On Semi-c-Periodic Functions - M. T. Khalladi; M. Kostić; M. Pinto; A. Rahmani; D. Velinov (Journal of Mathematics)
The main aim of this paper is to indicate that the notion of semi-c-periodicity is equivalent with the notion of c-periodicity, provided that c is a nonzero complex number whose absolute value is not equal to 1.